(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate selected hematological parameters from complete blood count in patients treated at the Department of Surgery, Thai Binh Medicial University Hospital, in 2024. Research and methods: A descriptive cross-sectional study was conducted on 452 medical records of patients admitted to the Department of Surgery, Thai Binh Medicial University Hospital between January and December 2024. Results: The ratio of male to female patients was 64.4% to 35.6%. The age group of 15-60 years accounted for the highest proportion, at 49.6%. The anemia rate among patients was 20.8%, with a higher rate in female patients compared to male patients (29.8% and 15.8%). There was one case of severe anemia diagnosed with gastric antrum ulcer, rectal ulcerative colitis, gout. Normal platelet counts were found in the majority of patients (92.3%), while thrombocytopenia was present in 5.3% of cases. Conclusion: Complete blood count is an inexpensive and clinically valuable test in routine practice. Beyond facilitating the early detection of hematological disorders, complete blood count also provides essential information for evaluating patients’ overall clinical status, prognosis, and postoperative monitoring. The findings further emphasize the necessity of incorporating regular health check-ups, including peripheral blood testing, into standard medical care. Early identification of anemia, hematological abnormalities, or other abnormal hematological parameters enables timely interventions, reduces perioperative complications, optimizes treatment outcomes, and ultimately improves patients’ quality of life.